Transgenic tobacco plant overexpressing ginkgo dihydroflavonol 4-reductase gene GbDFR6 exhibits multiple developmental defects - Ni, Jun; Zhang, Ning; Zhan, Yang; Ding, Kexin; Qi, Peng; Wang, Xuejun; Ding, Wona; Xu, Maojun (Frontiers in Plant Science, 2022)
Dihydroflavonol 4-reductase (DFR), a key enzyme in the flavonoid biosynthetic pathway in plants, significantly influences plant survival. However, the roles of DFR in the regulation of plant development are largely unknown. In the present study, phenotypes of transgenic tobacco plants overexpressing the Ginkgo biloba DFR gene, GbDFR6, were investigated. Transgenic tobacco seedlings exhibited relatively low fresh weights, long primary roots, decreased lateral root numbers, and impaired root gravitropic responses when compared to wild-type tobacco plants. Adult transgenic tobacco plants exhibited a considerably high percentage of wrinkled leaves when compared to the wild-type tobacco plants. In addition to the auxin-related phenotypic changes, transgenic tobacco plants exhibited delayed flowering phenotypes under short-day conditions. Gene expression analysis revealed that the delayed flowering in transgenic tobacco plants was caused by the low expression levels of NtFT4. Finally, variations in anthocyanin and flavonoid contents in transgenic tobacco plants were evaluated. The results revealed that the levels of most anthocyanins identified in transgenic tobacco leaves increased. Specifically, cyanidin-3,5-O-diglucoside content increased by 9.8-fold in transgenic tobacco plants when compared to the wild-type tobacco plants. Pelargonidin-3-O-(coumaryl)-glucoside was only detected in transgenic tobacco plants. Regarding flavonoid compounds, one flavonoid compound (epicatechin gallate) was upregulated, whereas seven flavonoid compounds (Tamarixetin-3-O-rutinoside; Sexangularetin-3-O-glucoside-7-O-rhamnoside; Kaempferol-3-O-neohesperidoside; Engeletin; 2'-Hydoxy,5-methoxyGenistein-O-rhamnosyl-glucoside; Diosmetin; Hispidulin) were downregulated in both transgenic tobacco leaves and roots. The results indicate novel and multiple roles of GbDFR6 in ginkgo and provide a valuable method to produce a late flowering tobacco variety in tobacco industry.